Towards an Integrative Definition of Scaling Social Impact in Social Enterprises - Islam, SM (Elsevier BV, 2020)
Scaling social impact is a key concept in the social enterprise literature. While central, the wide range of meanings and the lack of conceptual uniformity detract from its usefulness. To tackle this issue, this paper conducts a systematic review to derive an integrative definition of scaling social impact: Scaling social impact is an ongoing process of increasing the magnitude of both quantitative and qualitative positive changes in society by addressing pressing social problems at individual and/or systemic levels through one or more scaling paths. Alongside improving conceptual clarity, the definition offers an operational structure with five underlying elements, setting the basis for new empirical work and theorising in social enterprise research.
Keywords: Scaling social impact; Definition and concept; Construct clarity; Social enterprise; Social entrepreneurship; Social value